University Leadership, Abyssal Responsibility, Sovereign Exception: An Argument for a New Form of Disciplinary Decision-Making - Dronsfield, Jonathan (Stan Rzeczy, 2024)
A critique of university leadership, in particular as it is manifest in disciplinary processes. The basic problem is the separation of the leader from the institution she leads. Separation is an all-too-common problem with university leadership, and gives rise to a fundamental crisis of responsibility – what I name the problem of abyssal responsibility: a non-locatable responsibility for which no-one answers fully – making it unfairly difficult for the academic sanctioned to challenge the disciplinary decision. The gap created by the separation of the person deciding from evidence and reasons can be exploited for abusing power. In abyssal responsibility, the right to punish is intimately linked to the right to grant clemency, what I call sovereign exception. I ask whether the separation internal to the structure of abyssal responsibility might allow for a creative corrective to it. And I answer no, because then the only responsible decision would to abolish the leader. Responsibility in such cases must be made transparent and visible. I propose a form of leadership which is non-personalist and de-hierarchised, one which involves co-learning and co-responsivity, and above all is not separate. In short, a leadership which is democratic.